Awareness of pregnant women about proper nutrition habits and rational diet - Mandryk, Izabela; Węgrzyn, Izabella (Journal of Education, Health and Sport, 2023)
Introduction Proper nutrition of a woman before conception and during pregnancy determines the proper course of pregnancy, fetal development and the health of the mother and child in the future. A properly balanced diet must cover the increased demand for energy and provide the right amount and quality of nutrients. Aim The aim of the study was to verification the nutritional knowledge of pregnant women depending on age, place of residence and number of pregnancies. Results The survey involved 66 women between 19 and 40 years old (average age 30.50±4.30 years). 40.9% of the women were under 30 (N=27), and 59.1% of the respondents were 30 or older (N=39). 54.5% of women lived in cities (N=36), and 45.5% of the respondents lived in rural areas (N=30). Women who were pregnant for the first time accounted for 48.5% of the respondents (N=32). According to their own opinion, the majority of women (62.1%) stated that their knowledge of nutrition during pregnancy was good, and 28.8% assessed their knowledge as very good. The change in diet after pregnancy was confirmed by 81.8% of the surveyed women, in particular the changes concerned eating more vegetables and fruits (79.6%), avoiding highly processed products (61.1%) and avoiding sweets (50.0%). Most of the respondents (97.0%) indicated that they had eliminated products from their diet, i.e. alcohol (100.0%), Fast Food (57.8%) or sushi (60.9%). Snacks were eaten by 92.4% of the respondents, most often fruits (83.6%) and vegetables (63.9%). Conclusion Nutritional awareness of pregnant women is at a good level. Appropriate changes in their diet are declared by the majority of the surveyed women. It would be advisable to educate women planning pregnancy and pregnant women about the specific effects of essential nutrients and the risk of their deficiencies.